2011
DOI: 10.1590/s1984-29612011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Hepatozoon canis and Babesia canis vogeli in domestic dogs from Cuiabá, Brazil

Abstract: The objective of this study was to report for the first time infection by Hepatozoon spp. and Babesia spp. in 10 dogs from the city of Cuiabá, State of Mato Grosso, central-western Brazil. A pair of primers that amplifies a 574 bp fragment of the 18S rRNA of Hepatozoon spp., and a pair of primers that amplifies a 551 bp fragment of the gene 18S rRNA for Babesia spp. were used. Six dogs were positive for Babesia spp., and 9 were positive for Hepatozoon spp. Co-infection of Babesia spp. and Hepatozoon sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 13 publications
1
32
0
7
Order By: Relevance
“…After sequencing, the Babesia spp. found in dogs from Campo Grande showed 99% of identity with B. vogeli, which has already been found in dogs in the Brazilian states of Minas Gerais (PASSOS et al, 2005;COSTA-JÚNIOR et al, 2009), Pernambuco (RAMOS et al, 2010, Goiás (DUARTE et al, 2011) and Mato Grosso (SPOLIDORIO et al, 2011). Serological surveys revealed that the prevalence of antibodies to B. vogeli in dogs in Brazil ranged from 28.7% (COSTA-JÚNIOR et al, 2009) to 46.4% (VIEIRA et al, 2013).…”
Section: Igg Antibodies Tomentioning
confidence: 59%
“…After sequencing, the Babesia spp. found in dogs from Campo Grande showed 99% of identity with B. vogeli, which has already been found in dogs in the Brazilian states of Minas Gerais (PASSOS et al, 2005;COSTA-JÚNIOR et al, 2009), Pernambuco (RAMOS et al, 2010, Goiás (DUARTE et al, 2011) and Mato Grosso (SPOLIDORIO et al, 2011). Serological surveys revealed that the prevalence of antibodies to B. vogeli in dogs in Brazil ranged from 28.7% (COSTA-JÚNIOR et al, 2009) to 46.4% (VIEIRA et al, 2013).…”
Section: Igg Antibodies Tomentioning
confidence: 59%
“…These results largely contrast to all other regions of Brazil that have been investigated, where recent studies have indicated, by molecular methods, that a considerable proportion of the dogs was infected by E. canis, A. platys, B. vogeli, and/or H. canis (RAMOS et al, 2010;SPOLIDORIO et al, 2011;VIEIRA et al, 2011;COSTA-JÚNIOR et al, 2012;SILVA et al, 2012;DEMONER et al, 2013). Indeed, these results are directly related to the absence of infestations by R. sanguineus s.l.…”
Section: Discussionmentioning
confidence: 74%
“…Many recent studies have shown that canine babesiosis (caused by Babesia vogeli), hepatozoonosis (caused by Hepatozoon canis), monocytic ehrlichiosis (caused by Ehrlichia canis), and anaplasmosis (caused by Anaplasma platys) are endemic in many parts of the country (RAMOS et al, 2010;SPOLIDORIO et al, 2011;VIEIRA et al, 2011;COSTA-JÚNIOR et al, 2012;SILVA et al, 2012;DEMONER et al, 2013). While H. canis seems to be primarily associated with ticks of the genus Amblyomma in Brazil (FORLANO et al, 2007;DEMONER et al, 2013), the other agents mentioned above have been associated with Rhipicephalus sanguineus sensu lato ticks (DANTAS-TORRES, 2008;VIEIRA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the main tickborne pathogens that have been described for dogs are Babesia vogeli, Ehrlichia canis, Anaplasma platys, Hepatozoon canis, and Mycoplasma haemocanis (RAMOS et al, 2010;SANTOS et al, 2009;SPOLIDORIO et al, 2009SPOLIDORIO et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%